Implementation fidelity in leprosy care and support for disability prevention and management in Rupandehi, Nepal: A qualitative study - Sudip Nepal; Ari Probandari; Amit Timilsina; Anisha Shrestha; Prakash Chandra Joshi; Riris Ahmad Andono (PLoS ONE, 2025)
Background Implementation fidelity is critical for the efficient delivery of health services including leprosy services. Healthcare providers are important in monitoring the disease’s progression, managing complications, and cross-checking prescribed medications. This study explored implementation fidelity in leprosy care and support for disability prevention and management in Rupandehi district, Nepal. Methodology A qualitative case study design was adopted based on implementation research principles. From 25th February to 30th April 2024, data were collected through multiple sources and methods, including key informant interviews, focus group discussions, and observation. Semi-structured interview guidelines and qualitative checklists facilitated the data collection process. Participants were chosen using purposive and selective sampling methods. The data were inductively coded using qualitative analysis software. Thematic analysis was done with codes generated and aggregated to form sub-themes and develop themes. Results The study revealed that healthcare providers consistently adhered to national leprosy operational guidelines, ensuring sufficient fidelity by prompt multi-drug therapy, case diagnosis, complicated case referral, and regular follow-up. In contrast, poor adherence was demonstrated in the complication management of lepra reactions, ulcer cases, and self-care. The major barriers to leprosy services were financial hardship, complication management, pill burden, drug side effects, and institutional obstacles. In contrast, the facilitators to leprosy services included adequate human resources, treatment supporter’s involvement, effective communications, external development partner’s role, transportation incentives, and local government support. Conclusions Healthcare providers demonstrated sufficient adherence to leprosy operational guidelines. While significant gaps were evident in complication management, addressing financial and systematic barriers and leveraging facilitators is essential to strengthening leprosy care and support for disability prevention and management.